PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, KOMITMEN TUJUAN ANGGARAN, DAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perbankan di Kota Pekanbaru) - Utamy Riska Khairani; Azwir Nasir; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the direct effect of budgetary participation to managerial performance, and also indirect effect of budgetary participation to managerial performance with distributive fairness, procedural fairness, budget goal commitment and job relevant information as intervening variables. Collecting data of this study using a questionnaire submitted to111 lini manager/divisi/staff/employees who work at Perbankan in Pekanbaru. From questionnaires distributed 100 questionnaires (90%) ware completed and can be processed. Data analysis for hypothesis test was done with Partial Least Square (PLS). Result of this study give evidence that budgetary participation have significantly effect to managerial performance;it didn’t find indirect effect between budgetary participation to managerial performance through distributive justice and procedural fairness; budgetary participation have indirect effect to managerial performance through budget goal commitment and job relevant information.Keywords: participation, budgetary, performance, fairness, and commitment.